Quantitatively study on methane hydrate formation/decomposition process in hydrate-bearing sediments using low-field MRI. (15th February 2020) - Zhang, Yuying; Zhao, Yuechao; Lei, Xu; Yang, Mingjun; Zhang, Yi; Song, Yongchen
Abstract: In this paper, pure phase encoding low-field magnetic resonance imaging (MRI) methods were employed to quantitatively study the MH formation/decomposition process in partially water-saturated unconsolidated porous media, providing information about the hydrate-gas–water content, spatial distribution and occupancy changes within the pores. For MH formation, the temporal and spatial evolution of MH formation rate and distribution were not uniform due to inhomogeneous pore structure and fluid distributions, and heat and mass transfer differences; A hydrate film formed at the gas–water interface, increased the gas–water mass transfer resistance and inhibited further hydrate growth. The MH formation rate was also affected by the initial water saturation, and it decreased with increasing initial water saturation; The microscopic mechanism was that different initial water saturations led to different water distributions in the pores of different sizes and different degrees of heat and mass transfer, while the macroscopic phenomenon was reflected in the different periodic fast-slow evolution characteristics of the residual water saturation decreasing rate. The lower initial pore water saturation resulted in all water in some small pores consumed and converted to hydrate, while the higher one resulted in partial water in the medium and large pores consumed, and these pores were partially occupied by the formed quasi solid hydrate, increasing the surface-to-volume ratio and changing T2 distribution. For MH decomposition, in addition to the nonuniform heat and mass transfer, the temporal and spatial evolution of MH decomposition rate and distribution were also related to decomposed fluid migration due to gravity and capillary force effects.